Odyseusz – bohater o wielu twarzach (na podstawie Odysei Homera i Powrotu Odysa Stanisława Wyspiańskiego) - Wilczak, Wiktoria (Colloquia Litteraria, 2023)
The Return of Odysseus is a multifaceted drama, which speaks about the fate of man, about the impossibility of escaping from destiny. It is an interpretation of the Odyssey according to Wyspianski. Completely different, stripped of hypocrisy, true, showing a man, not a hero. It is also the most beautiful example of how much the playwright based his work on the legacy of antiquity, how much Greek culture mattered to him. It shows an incredible admiration and desire to understand antiquity, but also a desire to find in it himself, his own views, philosophy, spiritual path. Wyspianski proves that one’s own interpretations can lead to the discovery of new aspects of already known works. Every difference shown in this article proves how strong a link the two works share